MANAJEMEN PEMELIHARAAN BUS TRANSJAKARTA DALAM MENCAPAI STANDAR PELAYANAN MINIMUM - Ismiyati, Ismiyati; Firdaus, Miskul; Arubusman, Dian Artanti (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
This study aims to analyze the operational management system to improve the Transjakarta bis maintenance needs of safety and comfort for the user community. The method used is qualitative descriptive method. Results of the study: 1. Implementation of busway that has been and are going to be implemented by the local government of DKI Jakarta through the Department of Transportation (Dinas Perhubungan) and the Agency of Busway management (BP) has met the expectation like infrastructure such as ticketing system, bis stops, bis facilities, human resources and publications, 2. Performance in implementating busway program, in general has shown its satisfaction level. Busway is considered as an alternative public transport that is safe, comfortable and punctual, 3. Evaluation of the implementation of the busway program since last year have shown satisfying results. Busway passengers are around 17.4 million. 7.6 percent has shifted from private transportation to busway. It is higher than the average of shift rate in the world that is only 4 to 5 percent. The income from this program in 2015 for DKI Jakarta is Rp. 42.7 billion and it also has successfully changed peoples attitude to use public transportaion. However, congestion problem is not significantly decreased.